Możliwość wykorzystania endofitów w biologicznej ochronie roślin = The possibility of use of endophytes in biological plant protection - Katarzyna Koczwara; Dariusz Pańka; Karol Lisiecki; Marcin Juda (Kazimierz Wielki University, 2015)
Koczwara Katarzyna, Pańka Dariusz, Lisiecki Karol, Juda Marcin. Możliwość wykorzystania endofitów w biologicznej ochronie roślin = The possibility of use of endophytes in biological plant protection. Journal of Education, Health and Sport. 2015;5(6):333-340. ISSN 2391-8306. DOI 10.5281/zenodo.18699 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A333-340 https://pbn.nauka.gov.pl/works/567350 http://dx.doi.org/10.5281/zenodo.18699 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 16.06.2015.   Możliwość wykorzystania endofitów w biologicznej ochronie roślin   The possibility of use of endophytes in biological plant protection   Katarzyna Koczwara, Dariusz Pańka, Karol Lisiecki, Marcin Juda   Zakład Fitopatologii Molekularnej Uniwersytet Technologiczno-Przyrodniczy im. J.J. Śniadeckich w Bydgoszczy w Bydgoszczy     Streszczenie: Endofity są mikroorganizmami zasiedlającymi tkanki roślinne nie powodując choroby przynajmniej przez część swojego cyklu życiowego. Wpływają one pozytywnie na zasiedlaną roślinę, poprawiając jej plon i zwiększając odporność na czynniki stresowe. Dzięki zdolnościom do poprawy cech odpornościowych endofity mogą być wykorzystywane jako czynniki kontroli biologicznej w ochronie roślin przed szkodnikami, patogenami grzybowymi bądź nicieniami. Zwiększenie odporności na szkodniki może być uzyskane zarówno dzięki pasożytowaniu grzyba endofitycznego na szkodniku, jak również na syntezie związków zmniejszających żerowanie. Endofity wpływają również na zmniejszenie porażenia rośliny przez patogeny grzybowe. Na odporność roślin na nicienie wpływają zarówno endofity bakteryjne, jak i grzybowe. Zdolne są one do istotnego zmniejszenia uszkodzeń korzeni przez te organizmy. Aby dana asocjacja mogła być wykorzystana w biologicznej ochronie roślin musi cechować się stabilnością i zdolnością do istotnego zwiększenia odporności rośliny. Nie może być także szkodliwa dla ludzi i zwierząt gospodarskich. Słowa kluczowe: endofity, BCA, ochrona roślin, Neotyphodium, Beauveriabassiana.   Summary: Endophytes are microorganisms inhabiting plants without causing disease for at least part of their life cycle. They positively affect the plant, improving the yield and resistance to stress factors. Thanks to the ability to improve the plant resistance, endophytes can be used as biological control agents in plant protection against pests, nematodes or fungal pathogens. Increased resistance to pests can be achieved both by the parasiting on pest, as well as the synthesis of compounds that reduce the damage caused by insects. Endophytes also decrease the level of infection by fungal pathogens. Both bacterial and fungal endophytes affect plant resistance to nematodes. They are able to reduce the damage done to the roots by these organisms. Endophyte-plant association can be used in biological plant protection if it is stable and able to significantly increase the resistance of plants. It also have to be not harmful to humans and livestock. Key words: endophytes, BCA, plant protection, Neotyphodium, Beauveriabassiana.